DAUN KOPASANDA SEBAGAI TANAMAN ALTERNATIF PENANGKAL RADIKAL BEBAS - Maryam, St.; Widyawati, Widyawati; Angreni Putri, Uni; Lestari, Dian (Jurnal Kesehatan, 2021)
Kopasanda leaves (Chromolaena folium) are rich in flavonoids, including polyphenolic compounds that are closely related as substances that have the antioxidant capacity to ward off free radicals. Polyphenols in kopasanda include catechins, epicatechins, procyanidins and anthocyanidins. Kopasanda contains total phenols and a higher antioxidant capacity than wine or tea. So it is said that Kopasanda has high levels of antioxidants. The total antioxidant potential of the sample is determined by the ability to reduce iron (Fe) as a measure of "antioxidant strength". This study aims to examine the antioxidant activity and levels of flavonoid compounds in kopasanda leaves (Chromolaena folium), which will be analyzed using the FRAP method. The FRAP test was carried out by changing the blue color of FeII, a colorless tripyridyltriazine compound from FeIII that works to donate electrons. This method is widely used to analyze and determine the levels of antioxidants and flavonoid compounds in a plant. In the test, the absorbance results and the standard concentration of quercetin as a standard for antioxidant levels, from the linear regression results obtained the average value of the ethanol extract sample of kopasanda leaf (Chromolaena folium) of 16.914 mgQE/g extracts, meaning that in each gram of extract it is equivalent to 16.914 mg quercetin.